Waning vaccine immunity in teenagers primed with whole cell and acellular pertussis vaccine: Recent epidemiology - Sheridan, S.; Frith, K.; Snelling, Thomas; Grimwood, K.; McIntyre, P.; Lambert, S. (2014)
The recent epidemics of pertussis (whooping cough) in parts of the USA and Australia have led to the largest numbers of annual cases reported in over half a century. These epidemics demonstrated a new pattern, with particularly high rates of disease among pre-adolescents and early adolescents. These high rates of pertussis coincided with the first cohorts vaccinated with purely acellular pertussis vaccine, which replaced whole-cell pertussis (wP) vaccine in the later 1990s in the USA and Australia. Studies undertaken during these epidemics provide new evidence of more rapid waning of acellular pertussis-containing vaccines and longer-term protection from effective wP-containing vaccines. There is evidence that receiving wP as at least the first dose of pertussis-containing vaccine provides greater and more long-lived protection, irrespective of the nature of subsequent doses. This evidence will be reviewed together with the immunobiology associated with both vaccines, and the implications for pertussis control discussed. © 2014 Informa UK, Ltd.